Hubungan Kadar CRP dan Tekanan Darah Pada Wanita Obesitas di Wilayah Kerja Puskesmas Bagu - Adila Ika Rahmayati; Ari Khusuma; Erna Kristinawati; Pancawati Ariami (Journal of Indonesia Laboratory Students (JILTS), 2024)
Background: Body mass index (BMI) ≥30 kg/m² is defined as obesity II. Obese sufferers have a risk of increased blood pressure or hypertension, which is also associated with low-level inflammatory conditions. CRP is a test used to detect inflammatory processes, which can affect blood vessel damage. Research Objective: To determine the relationship between CRP levels and blood pressure in obese women in the Bagu Health Center Working Area. Research Methods: This research design is an analytical observational study with a cross sectional approach. By examining CRP levels using the latex agglutination method. Next, data analysis was carried out using bivariate tests. Results: The results of measurements of normal systolic blood pressure, prehypertension, hypertension I, hypertension 2, and hypertensive crisis were found respectively, namely 2 (9%), 6 (29%), 5 (24%), 7 (33%), 1 (5 %) and normal diastolic blood pressure-prehypertension, hypertension I, hypertension II respectively 7 (33%), 9 (43%), 5 (24%). With CRP levels of 5 (24%) respondents 6 mg/L and 16 (76%) respondents CRP negative. The results of data analysis show a relationship between CRP levels and systolic and diastolic blood pressure, namely <0.05 P-Value >α (α=0.05), which means there is no relationship between CRP levels and blood pressure in obese women in the Bagu Community Health Center working area. Conclusion: There was no relationship between CRP levels and blood pressure in obese women in the Bagu Community Health Center working area.